0.5x-0.6x+6=-1

Simple and best practice solution for 0.5x-0.6x+6=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.5x-0.6x+6=-1 equation:


Simplifying
0.5x + -0.6x + 6 = -1

Reorder the terms:
6 + 0.5x + -0.6x = -1

Combine like terms: 0.5x + -0.6x = -0.1x
6 + -0.1x = -1

Solving
6 + -0.1x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -0.1x = -1 + -6

Combine like terms: 6 + -6 = 0
0 + -0.1x = -1 + -6
-0.1x = -1 + -6

Combine like terms: -1 + -6 = -7
-0.1x = -7

Divide each side by '-0.1'.
x = 70

Simplifying
x = 70

See similar equations:

| (5/3)-y=4 | | -6(2t+8)=-24 | | 4(x-8)-(-9x-4)=12x | | 450/40 | | -3n+30=3(n-2) | | 5+5r=-5(5r-7) | | cosx=10/12 | | 20x+-5(x-1)=0 | | -14-m/6=0 | | 5+ln(x+5)=8 | | ad=9ax+12 | | 2(x+7)+8x=10x-14 | | 7-8x=-4+7(2-x) | | http://media.apexlearning.com/Images/200905/05/cad29818-fadd-43ca-80b4-6fc11707d1d5.gif | | 3y+5x=38 | | -2(3x+2)=-9-2x | | -7(z+2)=7-6x | | 10x+20-10=50 | | 40=5+x | | -40=x-2 | | -0.03x=-228 | | X-4=60 | | -0.03x= | | 5x+i=-17 | | 12x+32=12x-z | | 8b-15= | | 7x/10-x/2=1 | | 8b+15= | | 6(2x-1)-2(3x)=9 | | (-10+b)+(7b-5)= | | 70=.07x+X | | log5(√x/25) |

Equations solver categories